Taxonomy of the genus Commelina Plum. ex L. (Commelinaceae) in Nepal - Gajurel, Jyoti P; Shrestha, Krishna K (Botanica Orientalis: Journal of Plant Science, 2010)
About 170 species of Commelina are known from tropical and subtropical regions of the world. Nepal contributes 6 species of Commelina to the world flora. In the present work, taxonomy of all the six species of Commelina reported from Nepal (C. benghalensis, C. caroliniana, C. diffusa, C. maculata, C. paludosa and C. suffruticosa) was studied. Voucher specimens were collected from Central and Eastern Nepal, covering 14 districts. Morphological characters were studied from these collections. Palynological and anatomical characters were also used to see if they are taxonomically important to delimit the taxa within Commelina. Morphological characters seemed promising to delimit the taxa within Commelina. The key identifying characters at species level are modification in root, form of spathe, structure of leaves and seeds, shape of stomata and pollen. Palynological and anatomical characters were also useful, to some extent, in separating some species, but were not significant as compared to morphological data. Some specimens, close to C. benghalensis and C. caroliniana, showed very different characters. Thus further study is needed to confirm their taxonomic status. Key-words: anatomy; flora; morphological characters; palynology; voucher specimens. DOI: 10.3126/botor.v6i0.2907 Botanica Orientalis - Journal of Plant Science (2009) 6: 25-31